When Brands Take a Stand - Navigating Emotional Reactions to Brand Activism - Stefanie Wannow; Martin Haupt (Marketing Review St.Gallen, 2022)
Brands increasingly take a stand on controversial sociopolitical topics – and receive applause as well as severe backlash. Based on four clusters of moral emotions, this paper provides a framework for managers to better understand consumers' emotional responses to brand activism and design future campaigns more effectively.
Keywords: 650